The role of physical activity, stress, and lifestyle behaviors in adolescent mental health and well-being: A systematic review - Rahman, Dally; Edmizal, Eval; Denay, Naluri; Haryanto, Jeki; Dewi, Bunga Permata; Harahap, Asriandi (Jurnal Patriot, 2025)
Problem: Young people often face mental health troubles such as strain, sleep disturbances, and low existence satisfaction. Even though many research has proven that bodily activity can enhance mental fitness, it's miles nevertheless doubtful how bodily activity works collectively with different life-style elements like strain, weight-reduction plan, and social media use. Purpose: This study aims to summarize the effects of physical activity and related lifestyle factors on adolescent mental health. Methods: This study utilized a systematic literature review approach, gathering and analyzing scientific articles on the effects of regular physical activity influence the risk of depression among adolescents. Articles were sourced from Scopus using search terms such as "physical activity" OR exercise OR sport) AND (depression OR "mental health") AND (adolescent* OR teenager* OR youth with a focus on studies published within the past five years located in Indonesia. After collecting relevant articles, descriptive analysis was conducted to identify consistent patterns and findings. Results: This review discovered that better ranges of physical hobby had been linked to better mental health in youngsters. positive results protected reduced stress, better sleep excellent, higher existence pleasure, and extra resilience. then again, immoderate social media use, poor weight-reduction plan, and high strain stages were associated with worse mental fitness consequences. Environmental differences additionally played a position, with rural and concrete teens showing different patterns in physical and mental fitness. Conclusion: Physical activity allows improve mental health in youngsters. It reduces stress, improves sleep, and increases existence delight. on the same time, managing social media use, ingesting wholesome foods, and reducing stress are also essential. promoting healthy lifestyles can help higher mental nicely-being in young humans.